(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
One of the important aims of gas hydrate technology is to enhance the formation of hydrate or reduction the induction time for clathrate formation. The effect of the different promoter silica gel powder on R-134a gas hydrate formation has been investigated in the isochoric system experiment. It is noted that the purse media have a significant effect in increasing the speed of nucleation as well as improving the growth of hydrate. In the experiment, the effect of silica gel powder was studied to determine their effect on the composition and cooling capacity of 134 hydrates. From kinetic models were obtained many objective functions such as the amount of gas consumed (∆n), the growth rate (r (t)), and conversion of the water to hydrate. The gas consumed (∆n) of binary system increased with increase initial pressure of hydrate formation, also the hydrate growth rate (r (t)) and increase conversion of water to hydrate increase when this the first time that the effect of silica gel pweder on these functions with average active size (900) nm, BET surface area (0.65) m2/g, pore volume 210.85 cm3/g and average pore size (900) nm that studied for use in industrial applications and water treatment. The improvement of hydrate growth is marked by the addition of silica gel powder, which in turn increase the solubility of hydrate gas and reduce the contact angle. In addition, silica gel powder positively the contact with the gas through the increase of the interaction surface between gas and water and this increases the rate of formation of hydrate.